Anxiety and Self-care Behavior in Patients Undergoing Head and Neck Radiotherapy: Effect of Print and Multimedia Health Materials - Atefe Behboudifar; Fatemeh Heshmati Nabavi; Abdolghader Assarroudi (Mashhad University of Medical Sciences, 2018)
Background: Patients undergoing radiotherapy require training through educational media due to the specific nature of this therapeutic modality. Aim: The aim of this study was to compare the efficiency of multimedia and print educational tools in anxiety and self-care behaviors among patients undergoing radiotherapy. Method: This randomized clinical trial was conducted on 60 patients referring to the radiotherapy centers of Mashhad, Iran, in 2016. Based on the treatment centers, the patients were randomly assigned into two groups of Group 1 and 2 provided by a 20-minute multimedia training session and three pamphlets, respectively. The patients' anxiety was assessed in two stages, namely before the intervention and prior to the initiation of the first radiotherapy session, using the State-Trait Anxiety Inventory. Neil's Self-care Inventory was completed at the end of the first, third, and fifth weeks of treatment for assessing self-care behaviors. Results: The mean ages of the multimedia and pamphlet groups were 52.2±1.4 and 50.6±1.4, respectively. Paired t-test showed a significant decrease in the mean anxiety score of the pamphlet group (37.8±3.0) after the intervention, compared to that in the multimedia group (40.0±2.3) (P=0.009). Furthermore, the multimedia group had significantly higher self-care behavior scores, compared to the pamphlet group, in the first (P=0.003), third (P=0.01) and fifth weeks of treatment (P